2018
DOI: 10.3389/fendo.2018.00302
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin Signaling in the Podocyte: An Updated View of Signal Regulation at the Slit Diaphragm and Beyond

Abstract: Podocytes are a major component of the glomerular blood filtration barrier, and alterations to the morphology of their unique actin-based foot processes (FP) are a common feature of kidney disease. Adjacent FP are connected by a specialized intercellular junction known as the slit diaphragm (SD), which serves as the ultimate barrier to regulate passage of macromolecules from the blood. While the link between SD dysfunction and reduced filtration selectivity has been recognized for nearly 50 years, our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 162 publications
(215 reference statements)
0
114
0
1
Order By: Relevance
“…Several proteins are known to participate in maintaining the structural integrity and composition of slit diaphragm including NEPHRIN and NEPH1, whose genetic defects in humans and mice lead to FSGS, which is characterized by podocyte dysfunction and nephrotic range proteinuria [19,27,[34][35][36][37][38]. The prevailing hypotheses suggest that the extracellular domains of NEPHRIN and NEPH1 constitute the structural framework of slit diaphragm, thus, maintaining its structural integrity [17,37,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteins are known to participate in maintaining the structural integrity and composition of slit diaphragm including NEPHRIN and NEPH1, whose genetic defects in humans and mice lead to FSGS, which is characterized by podocyte dysfunction and nephrotic range proteinuria [19,27,[34][35][36][37][38]. The prevailing hypotheses suggest that the extracellular domains of NEPHRIN and NEPH1 constitute the structural framework of slit diaphragm, thus, maintaining its structural integrity [17,37,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…We now present compelling evidences that NEPHRIN and NEPH1 have receptor like properties, where they can be activated in a ligand-based fashion by HGF and are deactivated by the phosphatase SHP-2. Previous biochemical and genetic studies have shown that Src family kinases (SFK's) mediated tyrosine phosphorylations of NEPHRIN and NEPH1 cytoplasmic domains subsequently induce signal transduction events leading to podocyte actin cytoskeletal reorganization [16,18,36,41]. However, the activating and deactivating mechanisms that may regulate the phosphorylation of these proteins remain unknown [17,19,39].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, out of approximately 150 missense mutation of Nephrin annotated in the HGMD, nine mutations were reported in the cytoplasmic domain and an additional 25 mutations would produce truncations lacking all phosphorylation sites. Further, in multiple disease models, reduced Nephrin phosphorylation levels have been reported (Martin & Jones, 2018). However, it is still largely unknown how Nephrin signaling can result in the formation of the complicated structures seen in the slit diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrin is an essential structural component of the kidney glomerulus, a specialized structure for ultrafiltration of plasma, consisting of eight extracellular IgG repeats, a transmembrane domain, and an unstructured tail of ~160 amino acids (Martin & Jones, 2018, Ruotsalainen, Ljungberg et al, 1999. Nephrin maintains extracellular junctions between foot processes of podocyte cells in the kidney, while also regulating actin cytoskeletal support within the cells (Martin & Jones, 2018, Welsh & Saleem, 2010. At these interfaces, the eight extracellular IgG domains of Nephrin interact in-trans between cells to create an inter-digitating pattern of tight junctions that act as a biological filter (Gerke, 2003).…”
Section: Phosphorylation Of Nephrin Can Be Induced Using Fkbp-frb Hetmentioning
confidence: 99%
“…glomerular ultrafiltrate [7,8]. It is composed of proteins commonly found in tight and adherens junctions such as P-cadherin, zonula occludens-1 (ZO-1), and catenin family members, as well as proteins predominantly expressed in podocytes including nephrin, neph1, and podocin [7,8]. Both nephrin and neph1 are members of the immunoglobulin (Ig) superfamily [7].…”
mentioning
confidence: 99%